MAPPING OF YOGYAKARTA CITY'S MSME READINESS FOR GOVERNMENT PROGRAMS, PROMOTIONS AND EXHIBITIONS : LEGALITY, MANAGEMENT, AND MARKET ORIENTATION - Hafidh Rifky Adiyatna (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
This study aims to map the level of readiness of Micro, Small, and Medium Enterprises (MSMEs) in Yogyakarta City in the context of promotion and exhibition facilitation through indicators of market readiness, governance readiness, and administrative readiness. The study used a descriptive quantitative approach with a cross-sectional survey design. Data sourced from a structured questionnaire completed by 452 MSMEs were analyzed using descriptive statistics in the form of frequency tabulations, percentages, summary measures of central tendency, and cross-tabulations. The results showed that the composition of respondents was dominated by the culinary sector (51.1%), and most MSMEs started their businesses in the 2016–2019 period. A total of 70.6% of MSMEs have a digital marketing platform, but its use is still concentrated on one main channel, primarily Instagram. Target market orientation is still dominated by the local market (58.2%), while orientation covering the international market is relatively small. From a governance aspect, the majority of MSMEs do not have a vision (66.2%) and have not set annual targets (59.1%), potentially weakening the focus and measurement of the success of promotional programs. In terms of administrative readiness and promotional experience, 56.9% of MSMEs have a Business Identification Number (NIB). However, the majority have never participated in an exhibition/expo (71.7%). Descriptively, MSMEs with a vision and annual targets tend to be better prepared in other aspects, such as legality, digital platform adoption, expo experience, and median turnover. The study recommends a phased facilitation model that includes accelerating legality, core promotional training, strengthening integrated digital marketing channels, and pre- and post-exhibition curation and mentoring to ensure promotions have a sustainable impact.